IMPLEMENTASI LIKUIDASI KORPORASI DI INDONESIA: KAJIAN AKUNTANSI DAN YURIDIS - Nurul Hidayah; Amrie Firmansyah (Fakultas Ekonomi, Universitas Negeri Jakarta, 2020)
This study aims to analyze corporate liquidation accounting practices in Indonesia. The method employed is qualitative. The approach used in the study was interviews with two informants, namely accounting practitioners and legal experts. The data obtained from the two informants were analyzed based on suitability with theory, related literature both from the accounting and juridical sides. This study concludes that, in general, Law Number 40 of 2007 has provided guidelines regarding liquidation procedures and liquidator responsibilities, but Indonesia's financial accounting standards do not regulate guidelines for corporate liquidation. Based on this study's results, the Government needs to formulate a more comprehensive regulation on company liquidation. Also, the Indonesian Institute of Accountants needs to set financial accounting standards related to corporate liquidation.